Reflexivity in Health Promotion: A Typology for Training. Issue 4 (July 2020) - Alexander, Stephanie A.; Jones, Catherine M.; Tremblay, Marie-Claude; Beaudet, Nicole; Rod, Morten Hulvej; Wright, Michael T.
Reflexivity has emerged as a key concept in the field of health promotion (HP). Yet it remains unclear how diverse forms of reflexivity are specifically relevant to HP concerns, and how these "reflexivities" are interconnected. We argue that frameworks are needed to support more systematic integration of reflexivity in HP training and practice. In this article, we propose a typology of reflexivity in HP to facilitate the understanding of reflexivity in professional training. Drawing from key theories and models of reflexivity, this typology proposes three reflexive positions (ideal-types) with specific purposes for HP: reflexivity in, on, and underlying action. This article illustrates our typology's ideal-types with vignettes collected from HP actors working with reflexivity in North America and Europe. We suggest that our typology constitutes a conceptual device to organize and discuss a variety of experiences of engaging with reflexivity for HP. We propose the typology may support integrating reflexivity as a key feature in training a future cadre of health promoters and as a means for building a responsible HP practice.